2014
DOI: 10.3171/2013.12.jns131089
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a noninvasive cerebral oxygenation monitor in patients with severe traumatic brain injury

Abstract: Measuring regional cerebral tissue oxygenation with the CerOx monitor in a noninvasive manner is feasible in patients with severe TBI in the neurointensive care unit. The correlation between the CerOx measurements and the jugular bulb venous measurements of oxygen saturation indicate that the CerOx may be able to provide an estimation of cerebral oxygenation status in a noninvasive manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…In this study, no comment was made on the clinical significance of these events and any differing agreement between the modalities with tissue hypoxia of differing magnitude. A largely negative outcome was reported in a more recent investigation by Rosenthal and coworkers 40 that evaluated the effectiveness of NIRS technology when combined with ultrasound pulsing against invasive multimodal monitoring in 18 patients with severe TBI. They concluded that the parameters recovered by NIRS did not correlate to PbrO 2 consistently (using the Licox Ò system).…”
Section: Davies Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, no comment was made on the clinical significance of these events and any differing agreement between the modalities with tissue hypoxia of differing magnitude. A largely negative outcome was reported in a more recent investigation by Rosenthal and coworkers 40 that evaluated the effectiveness of NIRS technology when combined with ultrasound pulsing against invasive multimodal monitoring in 18 patients with severe TBI. They concluded that the parameters recovered by NIRS did not correlate to PbrO 2 consistently (using the Licox Ò system).…”
Section: Davies Et Almentioning
confidence: 99%
“…They concluded that the parameters recovered by NIRS did not correlate to PbrO 2 consistently (using the Licox Ò system). These three aforementioned studies 15,19,40 utilized the Licox (Clarke cell based) system for PbrO 2 monitoring, without frequency domain or depth-resolved NIRS data acquisition. To date, no study has compared these modalities using either the alternative systems of measuring PbrO 2 or any of the data manipulation techniques discussed, including better depth-resolved outputs such as the TOI and THI.…”
Section: Davies Et Almentioning
confidence: 99%
“…It remains uncertain whether neuroimaging provides additional or similar information as continuous neuromonitoring utilizing invasive probes [13][14][15][16][17][18][19] or noninvasive cerebral hemodynamic and electrophysiologic methods [20][21][22][23]. While a detailed discussion of the latter methods is outside the scope of this review, multiple imaging studies have sought to assess how imaging may facilitate detection of edema, tissue shifts, and herniation in order to guide management.…”
Section: Head Computed Tomographymentioning
confidence: 99%
“…In this vein, Leal-Noval et al 25 illustrated that PbtO 2 and rSO 2 are significantly related, but concluded that NIRS diagnostic accuracy is too limited and not sensitive enough regarding small changes in cerebral oxygenation to replace invasive PbO 2 monitoring. Studies examining the correlation of NIRS measures to jugular bulb venous oxygen saturation, [26][27][28] as well as microdialysis, 29 show a similar degree of uncertainty, largely due to technological limitations of the NIRS monitoring devices as well as difficulties in computational methodology.…”
Section: Near-infrared Spectroscopy For Monitoring Cerebral Autoregulmentioning
confidence: 99%